(Re)reading Travail et travailleurs en Algérie. The relevance of one of Pierre Bourdieu’s lesser-known books - Pinna, Gabriele (Cambio. Rivista sulle Trasformazioni Sociali, 2022)
Twenty years after the death of Pierre Bourdieu, his vast corpus continues to fuel lively debates on an international level. Over the last few years, several scholars have been interested in the link between Bourdieu and the sociology of work and the legacy of his conceptual apparatus for the sociological study of Labor. In 2021, in France, one of his lesser-known books, Travail et travailleurs en Algérie, was republished in an updated version. This critical reading pursues a triple objective: to highlight how, firstly, already in this early phase of his career, Bourdieu began to define some of the methodological and epistemological assumptions of his sociology: the relevance of reflexivity; a methodological approach that combines ethnography and statistics, overcoming the sterile contrast between objectivism and subjectivism; an idea of sociology that crosses the frontiers between the social sciences and disciplinary specializations. Secondly, the analysis of this book allows us to retrace the genesis of the concept of habitus, starting from the influence exercised on Bourdieu by Weber’s study on the link between Protestant ethics and the spirit of capitalism. Finally, the re(reading) of Travail et travailleurs en Algérie consent to describe the substantially positive meaning that Bourdieu attributes to work, as an activity, and even more to employment in contemporary capitalist societies.